PROFESIONALISME, RESPONSIVITAS DAN KREDIBILITAS PEGAWAI KANTOR KECAMATAN TERHADAP KEPUASAN MASYARAKAT FENAFAFAN KABUPATEN BURU SELATAN - TEHUBIJULUW ZACHARIAS (Fakultas Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to determine the partial and simultaneous influence of professionalism,responsiveness and credibility District Office employees on community satisfaction. Thisresearch was designed using descriptive verification research type. the population in this studywere all people in the Fenafafan Subdistrict who received services in 2019 at the time the studytook place as many as 172 people. The determination of the sample is based on the Slovinformula and is determined by simple random sampling. The number of samples based on Slovinformula with a tolerance limit of 10%, as many as 64 people. Data were analyzed by multiplelinear regression. The results showed that professionalism, responsiveness and credibility ofFenafafan District Office staff had a significant positive effect on community satisfactionpartially and simultaneously, with professionalism as the dominant variable.